Advanced Numerical Modeling and Experimental Analysis of Thermal Gradients in Gleeble Compression Configuration for 2017-T4 Aluminum Alloy - Olivier Pantalé; Yannis Muller; Yannick Balcaen (Applied Mechanics)
Gleeble thermomechanical simulators are widely utilized tools for the investigation of high-temperature deformation behavior in materials. However, temperature gradients that develop within the specimen during Gleeble compression tests have the potential to result in non-uniform deformation, which may subsequently impact the accuracy of the measured mechanical properties. This study presents an experimental and numerical investigation of the temperature fields in 2017-T4 aluminum alloy specimens prior to Gleeble compression tests at temperatures ranging from <semantics>300 °C to 500 °C</semantics> utilizing uniform temperature distribution (ISO-T) tungsten carbide anvils. The use of multiple thermocouples, welded to both the specimen and anvils, offers valuable insights into the temperature gradients and their evolutions. A coupled thermal–electrical finite-element model was developed in Abaqus for the purpose of simulating the resistive heating process. A user amplitude subroutine (UAMP) is implemented to regulate the heating based on a proportional–integral–derivative (PID) algorithm that modulates the current density to follow the specified temperature profile. The numerical results demonstrate that the temperature gradients within the specimen at the end of the heating process, reaching a temperature of <semantics>400 °C</semantics>, are minimal, with values below <semantics>1.9 °C</semantics>. This is in accordance with the experimental observations. The addition of graphite foils between the specimen and anvils has been shown to effectively reduce the gradients. The use of the measured anvil temperature as a boundary condition, rather than a constant value of <semantics>20 °C</semantics>, has been demonstrated to improve the agreement between the simulated and experimental cooling curves. The modeling approach provides a framework for quantifying temperature gradients in Gleeble compression specimens and for assessing their impact on the measured constitutive response of materials at elevated temperatures.